Understanding the AC Equivalent Circuit Response of Ultrathin Cu(In,Ga)Se2 Solar Cells - Cunha, Jose M.V. (2019)
This paper aims to study the ac electrical response of standard-thick, ultrathin, and passivated ultrathin Cu(In,Ga)Se 2 (CIGS) solar cells. Ultrathin CIGS is desired to reduce production costs of CIGS solar cells. Equivalent circuits for modeling the behavior of each type of solar cells in ac regime are based on admittance measurements. It is of the utmost importance to understand the ac electrical behavior of each device, as the electrical behavior of ultrathin and passivated ultrathin CIGS devices is yet to be fully understood. The analysis shows a simpler ac equivalent circuit for the ultrathin device without passivation layer, which might be explained by the lowered bulk recombination for thin-film CIGS solar cells when compared with reference thick ones. Moreover, it is observed an increase in shunt resistance for the passivated ultrathin device, which strengthens the importance of passivation for shunts mitigation when compared with unpassivated devices.